2020
DOI: 10.1101/2020.03.25.20043133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of hypertension, diabetes and coronary heart disease on COVID-19 diseases severity: a systematic review and meta-analysis

Abstract: Background COVID-19 patients with chronic diseases such as hypertension, diabetes and coronary heart diseases is more likely to worsen, but with mixed results for COVID-19 severity. This meta-analysis is to analyze the correlation between hypertension, diabetes, coronary heart disease and COVID-19 disease severity.Methods Available data from PubMed, Web of Science, China National Knowledge Infrastructure Database, WanFang Database and VIP Database, were analyzed using a fixed effects model meta-analysis to der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 19 publications
6
122
0
11
Order By: Relevance
“…35-4.05; p = 0.002) for acute respiratory distress syndrome (ARDS) [2] has been reported. Further, meta-analysis of nine studies from China (n = 1936) showed a significant correlation between severity of COVID-19 and diabetes (OR, 2.67, 95% CI; 1.91-3.74; p < 0.01) [3]. Similarly, case fatality rate was 7.3% in patients with diabetes as opposed to 2.3% in those without diabetes in a report of 44,672 patients of COVID-19 by Chinese Centre for Disease Control [4].…”
Section: Why Patients With Diabetes Have Increased Severity and Mortamentioning
confidence: 97%
“…35-4.05; p = 0.002) for acute respiratory distress syndrome (ARDS) [2] has been reported. Further, meta-analysis of nine studies from China (n = 1936) showed a significant correlation between severity of COVID-19 and diabetes (OR, 2.67, 95% CI; 1.91-3.74; p < 0.01) [3]. Similarly, case fatality rate was 7.3% in patients with diabetes as opposed to 2.3% in those without diabetes in a report of 44,672 patients of COVID-19 by Chinese Centre for Disease Control [4].…”
Section: Why Patients With Diabetes Have Increased Severity and Mortamentioning
confidence: 97%
“…The most common comlaints at prsentaion were shortness of breath (56.7%), caugh (45.9%), fever (37.4%), and tiredness (23.3%). At admission, lack of consciousness and O2 saturation less than 93% were observed in 5.7% (26) Compared to survivors, patients who dead (non-survivors) were signi cantly older (mean (SD) age: 69.4 years (12.2) vs. 62.6 years (13.5); P < 0.001), were more likely to have underlying comorbidity CKD (35.4% (28) vs. 19.4% (73); P= 0.002). In terms of numbers of comorbidities, a higher percentage of non-survivors had 3 or more comorbidities (22.8 vs. 12.5%; P= 0.008) than survivors.…”
Section: Resultsmentioning
confidence: 96%
“…patients [8,25,26]; however no study focused on biochemical indicators as predicting factors for death in diabetic infected patients, presenting the optimal cutoff points to discriminate between survivors and nonsurvivors. Among laboratory parameters for predicting death, neutrophil and lymphocyte count as indicators for immune function and LDH level as a marker of tissue breakdown had the highest diagnostic accuracy in infected diabetic patients.…”
Section: Previous Studies Have Been Indicated Diabetes As a Risk Factmentioning
confidence: 99%
“…The defect of cellular immune response and cytokine storm may play roles in the development of acute respiratory distress syndrome [17]. Since diabetic patients suffer from a less robust immune system due to chronic hyperglycemic and in ammatory states, DM could be a risk factor for COVID-19 progression and death [17][18][19][20] Moreover, there are con icting results regarding the use of angiotensin-converting enzyme 2 (ACE2)-increasing drugs in COVID-19 patients [20,21]. Some studies proposed the harmful effects of these drugs on infection severity while the other ones found the drugs useful for preventing pneumonia and the risk of mortality [16,22].…”
Section: Discussionmentioning
confidence: 99%